TOWARD A TRIPLE BOTTOM LINE: A REVIEW OF SUSTAINABILITY PRACTICES IN THE PALM OIL SUPPLY CHAIN - Judijanto, Loso (Editora Impacto Científico, 2025)
Facing mounting international demands, the palm oil industry is compelled to pursue sustainability efforts that equitably address economic viability, environmental stewardship, and societal impact. The study examines how the economic, environmental, and social pillars of the Triple Bottom Line (TBL) framework are reflected across the entire palm oil value chain. The research adopts a qualitative approach using a Systematic Literature Review (SLR), guided by the PRISMA protocol. Data were collected from the ScienceDirect database using targeted keyword combinations. An initial search yielded 825 results, refined to 31 eligible peer-reviewed, open-access research articles published between 2021 and 2025. The review followed a four-stage screening: keyword relevance, publication year, article type (research articles only), and accessibility (open access/archive). Data were analysed thematically to extract patterns, gaps, and interconnections between sustainability practices and TBL principles. The findings indicate significant progress in the economic and environmental areas, including increased yield efficiency, reduced emissions, and improved traceability enabled by digital tools. However, social aspects such as labour conditions, gender equity, and smallholder inclusion remain insufficiently addressed. In conclusion, while sustainability efforts have intensified, a more integrated and inclusive approach is required, particularly for marginalised stakeholders. Future research should investigate the long-term outcomes of certification schemes, the role of local governance in implementing TBL, and the potential of emerging technologies to bridge existing sustainability gaps. DOI: https://doi.org/10.56238/edimpacto2025.084-024